Algorithmic Foundation of Robotics VIII Selected Contributions of the Eight International Workshop on the Algorithmic Foundations of Robotics - Chirikjian, Gregory S.; Choset, Howie; Morales, Marco; Murphey, Todd.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume is the outcome of the eighth edition of the biennial Workshop on Algorithmic Foundations of Robotics (WAFR). Edited by G.S. Chirikjian, H. Choset, M. Morales and T. Murphey, the book offers a collection of a wide range of topics in advanced robotics, including networked robots, distributed systems, manipulation, planning under uncertainty, minimalism, geometric sensing, geometric computation, stochastic planning methods, and medical applications. The contents of the forty-two contributions represent a cross-section of the current state of research from one particular aspect: algorithms, and how they are inspired by classical disciplines, such as discrete and computational geometry, differential geometry, mechanics, optimization, operations research, computer science, probability and statistics, and information theory. Validation of algorithms, design concepts, or techniques is the common thread running through this focused collection. Rich by topics and authoritative contributors, WAFR culminates with this unique reference on the current developments and new directions in the field of algorithmic foundations.
Networks -- Probabilistic Network Formation through Coverage and Freeze-Tag -- Planning Aims for a Network of Horizontal and Overhead Sensors -- Mobile Wireless Sensor Network Connectivity Repair with K-Redundancy -- Distributed Systems -- On Endogenous Reconfiguration in Mobile Robotic Networks -- Simultaneous Control of Multiple MEMS Microrobots -- Simultaneous Coverage and Tracking (SCAT) of Moving Targets with Robot Networks -- Cooperative Towing with Multiple Robots -- Manipulation -- Two Finger Caging: Squeezing and Stretching -- A State Transition Diagram for Simultaneous Collisions with Application in Billiard Shooting -- A Variational Approach to Strand-Based Modeling of the Human Hand -- A Stopping Algorithm for Mechanical Systems -- Robust Planning -- Perceived CT-Space for Motion Planning in Unknown and Unpredictable Environments -- Bounded Uncertainty Roadmaps for Path Planning -- A Sampling Hyperbelief Optimization Technique for Stochastic Systems -- Computational Minimalism -- On the Value of Ignorance: Balancing Tracking and Privacy Using a Two-Bit Sensor -- On the Existence of Nash Equilibrium for a Two Player Pursuit-Evasion Game with Visibility Constraints -- On the Topology of Plans -- Geometric Sensing -- Mirror-Based Extrinsic Camera Calibration -- On the Analysis of the Depth Error on the Road Plane for Monocular Vision-Based Robot Navigation -- Sensor Beams, Obstacles, and Possible Paths -- A Motion Planner for Maintaining Landmark Visibility with a Differential Drive Robot -- Geometric Computations -- On Approximate Geodesic-Distance Queries amid Deforming Point Clouds -- Constrained Motion Interpolation with Distance Constraints -- Generating Uniform Incremental Grids on SO(3) Using the Hopf Fibration -- A Simple Method for Computing Minkowski Sum Boundary in 3D Using Collision Detection -- Polyhedral Assembly Partitioning with Infinite Translations or The Importance of Being Exact -- Realistic Reconfiguration of Crystalline (and Telecube) Robots -- Kinodynamic Motion Planning by Interior-Exterior Cell Exploration -- Stochastic Methods in Planning -- Control of Probabilistic Diffusion in Motion Planning -- Stochastic Motion Planning and Applications to Traffic -- On Probabilistic Search Decisions under Searcher Motion Constraints -- Planning with Reachable Distances -- Medical Applications -- 3D Motion Planning Algorithms for Steerable Needles Using Inverse Kinematics -- Modeling Structural Heterogeneity in Proteins from X-Ray Data -- Minimum Resource Characterization of Biochemical Analyses for Digital Microfluidic Biochip Design -- Path Planning for Flexible Needles Using Second Order Error Propagation -- Planning -- Path Planning among Movable Obstacles: A Probabilistically Complete Approach -- Multi-modal Motion Planning in Non-expansive Spaces -- Toward SLAM on Graphs -- HybridSLAM: Combining FastSLAM and EKF-SLAM for Reliable Mapping -- Discovering a Point Source in Unknown Environments.
Keywords: Engineering; Artificial intelligence; Systems theory; Engineering; Control, Robotics, Mechatronics; Artificial Intelligence (incl. Robotics).; Machinery and Machine Elements; Systems Theory, Control